Decolonising the future in the untransformed present in South African higher education - Fomunyam, Kehdinga George (Faculty of Education, University of the Free State, 2017)
South Africa as a nation became democratic in 1994 because of the end of apartheid. Since 1994, higher education has geared towards transformation and redress of the inequalities created by the inhuman policies of apartheid. While few applaudable steps have been taken towards this direction, South African higher education remains largely untransformed. For the past two years, a wave of student protest swept across the nation, calling for decolonisation of higher education in general and the curriculum in particular. This move brings to mind several questions about decolonisation and transformation. What is the state of South African higher education? Why has it remained untransformed since the advent of democracy? What should be decolonised to ensure transformation of the present and the future? This paper therefore ventures to answer these three questions using the theory of social transformation as a lens. The paper points out that funding structures, research politics, administrative structures and a lack of interest are amongst the reasons for the lack of transformation. The paper concludes that there will be no transformation until higher education institutions have been decolonised. Social transformation is therefore argued as the pathway for decolonisation. The paper recommends that transformation in higher education should go beyond the shelves where they are stored as policy to the classroom and university environment for practice and universities need to revise their understandings of transformation under the guidance of the DHET.
Keywords: Decolonisation; South African higher education; Transformation; Universities